Time Capsule: Artifacts for Documentation of the Paradigm Shift - F. Todd Goodson (Educational Considerations, 2021)
This issue of Educational Considerations is comprised of three manuscripts offering different applications of the tools of the historian within education. Educators have a long and unfortunate history of ignoring their own history. Time and again, we pay a price for this in a variety of ways.
Keywords: Education; history